2012
DOI: 10.3382/ps.2011-01931
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pullet body weight, dietary nonpyhtate phosphorus intake, and breeder feeding regimen on production performance, chick quality, and bone remodeling in broiler breeders

Abstract: A 3 × 2 × 2 factorial experiment, consisting of 52 hens per treatment, was conducted to determine the effects of pullet BW, dietary nonphytate phosphorus (NPP), and feeding regimen on performance, progeny quality, and bone remodeling. Cobb 500 broiler breeder pullets were reared to 3 different growth curves: 20% under, Cobb standard, and 20% over. Body weights were recorded weekly and feed adjustments made accordingly. At 21 wk, 624 hens were fed one of 2 breeder diets differing only in the amount of dietary N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
3
10
0
1
Order By: Relevance
“…No effects of rearing photoperiod on egg weight have been reported before. Previous studies showed that an increased 20 wk BW target did not affect egg weight (Fattori et al, 1991 ; Hocking et al, 2001 , 2002 ; Gous and Cherry, 2004 ; Robinson et al, 2007 ; Ekmay et al, 2012 ; van Emous et al, 2013 ), where others showed that a 20% increased BW at 20 wk of age increased egg weight by about 1 g (Renema et al, 2001a , 2001b ; Sun and Coon, 2005 ). We are currently unsure about the possible explanation of the described interaction.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…No effects of rearing photoperiod on egg weight have been reported before. Previous studies showed that an increased 20 wk BW target did not affect egg weight (Fattori et al, 1991 ; Hocking et al, 2001 , 2002 ; Gous and Cherry, 2004 ; Robinson et al, 2007 ; Ekmay et al, 2012 ; van Emous et al, 2013 ), where others showed that a 20% increased BW at 20 wk of age increased egg weight by about 1 g (Renema et al, 2001a , 2001b ; Sun and Coon, 2005 ). We are currently unsure about the possible explanation of the described interaction.…”
Section: Resultsmentioning
confidence: 92%
“…Independent of photoperiod, higher than recommended BW at the end of rearing accelerated sexual maturity (age at first egg), whereas a lower than recommended BW delayed sexual maturity (Fattori et al, 1991 ; Renema et al, 2001a , b ; Hocking, 2004 ; Ekmay et al, 2012 ). However, other studies did not find the same result (Zuidhof et al, 2007 ; van Emous et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in chickens, elevated ALP activity has been predominantly related to increased osteoblastic activity and used as a marker for evaluating skeletal health and bone disease, such as skeletal growth, rickets, fracture repair, and osteomyelitis ( Lumeij and Westerhof, 1987 ). More recently, Ekmay et al. (2012) used ALP serological levels to assess broiler breeder growth and bone mineral deposition during transition into sexual maturity (24–26 wk of age).…”
Section: Discussionmentioning
confidence: 99%
“…Van Emouset al 2018reported that age at sexual maturity was not affected by differences in daily CP intake in broiler breeders. On the other hand, Ekmay et al (2012) described the relation between body weight and sexual maturity who reported that the age at sexual maturity decreased with the increasing of body weight in broiler breeders.…”
Section: Body Weight Gainmentioning
confidence: 99%